Development of "Immersion and Plated Filtering" as an Alternative of VCO Making - Dalmadi Dalmadi (Jurnal Biologi Tropis, 2019)
The purpose of this study was to determine the quality of VCO oil made using the Layered Induction and Filtering technique. This research is an experimental study using the Layered Induction and Filtering method in making VCO oil. The population used as the object of this research is coconut in the Mataram city area, which is the raw material for making VCO oil. While the sample used is old and dry coconut fruit. The data from the calculation of the VCO quality test were obtained using the standard formula for calculating the quality of oil to test for moisture, peroxide numbers and free fatty acids. The results of the water content test at an interval of one hour for four times were 0.15%, the test results for the peroxide number were 2.46 and the acid number test results were 0.46%. Based on APCC (Asian and Pacific Coconut Community) standards, VCO oil made with the Layered Induction and Filtering technique has the quality of the water content, peroxide number, and free fatty acids below the maximum standards set by APCC, so the quality of VCO oil is very good. Making VCO with this method can be applied on a household scale with the quality of results according to the standards set by the APCC.